КЕРУВАННЯ НАПРУГОЮ ЖИВЛЕННЯ ДАТЧИКІВ ХОЛЛА У МАГНІТОЕЛЕКТРИЧНИХ СИСТЕМАХ МАЛОЇ ПОТУЖНОСТІ - Акинін, К.П.; Антонов, О.Є.; Кіреєв, В.Г. (Інститут електродинаміки Національної академії наук України, 2019)
The methods of control of the supply voltage of the Hall sensor system are developed and investigated when reducing the time of sensors operation without information losing about the rotor position of a permanent magnet brushless motor. Using of such approaches allow increase the efficiency of low power magneto-electric systems and minimize hardware part of their supply sources. References 7, figures 7.